Lessons from the crisis in Argentina - Daseking, Christina; International Monetary Fund (Washington, D.C.: International Monetary Fund, 2004)
This paper examines economic crisis that hit Argentina (2001-20025). During this period, output fell by about 20 percent over three years, inflation reignited, the government defaulted on its debt, the banking system was largely paralysed. In the early months of 2003, the economy began to recover, but there remained a long road back to sustained growth and stability. It details the crisis from the origins to its evolution until early 2002. It analyses the economic forces, including a prolonged recession, leading up to the crisis and draws general policy lessons, both for countries' efforts to prevent such crises, and for the IMF's surveillance and use of its financial resources
Overview -- Boom years and buildup of vulnerabilities: 1992-98 -- Downturn and deepening depression: 1998-2000 -- Crisis: 2001 -- Aftermath: 2002 -- Role of the IMF -- Conclusions -- Appendix I: Argentina's potential output growth -- Appendix II: Chronology of key developments in 2001-2002.
Includes bibliographical references
lje 09/0913
Loans
Keywords: Argentina; Monetary Crisis; Economic Recession